Exploiting the Potential of Hidden Web for Competitive Advantage - Pawełoszek-Korek, Ilona (Wykorzystanie potencjału ukrytej sieci WEB do osiągnięcia przewagi konkurencyjnej, 2009)
Most of the approaches described in scientific literature consider the notion of Hidden Web as a challenge for scholars and developers looking for hidden information and working out the applications for crawling Hidden Web. The approach presented here shows the issue of Hidden Web in different way – from the point of view of an e-business entrepreneur.The objective of this paper is to explore the theoretical and practical issues associated with gaining competitive advantage for Web portals by exploiting an e-business model using Hidden Web resources.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 55, s. 304-316
Keywords: Hidden Web; competitive advantage; e-business model